2019
DOI: 10.1177/1178626419842176
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Insulin-Like Growth Factors and Insulin-Like Growth Factor–Binding Proteins in the Nervous System

Abstract: The insulin-like growth factors (IGF-I and IGF-II) and their receptors are widely expressed in nervous tissue from early embryonic life. They also cross the blood brain barriers by active transport, and their regulation as endocrine factors therefore differs from other tissues. In brain, IGFs have paracrine and autocrine actions that are modulated by IGF-binding proteins and interact with other growth factor signalling pathways. The IGF system has roles in nervous system development and maintenance. There is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 374 publications
(468 reference statements)
0
95
0
1
Order By: Relevance
“…Insulin-like growth factor (IGF-1) is an important regulator of cell growth, which is widely present in human cytoplasm, extracellular and transmembrane regions, and is a glycoprotein transmembrane receptor. According to relevant research results, IGF-1 is abnormally expressed in breast cancer, ovarian cancer and other malignant tumor tissues and can promote the proliferation of tumor cells [12,13], but it has not been reported in the study on the mechanism of diabetes. In patients with diabetes, IGF-1 signal transduction can change the adhesion of cells and lead to malignant development of cells.…”
Section: Immunohistochemistry Analysis Of Igf-1 Expression In Islet Tmentioning
confidence: 99%
“…Insulin-like growth factor (IGF-1) is an important regulator of cell growth, which is widely present in human cytoplasm, extracellular and transmembrane regions, and is a glycoprotein transmembrane receptor. According to relevant research results, IGF-1 is abnormally expressed in breast cancer, ovarian cancer and other malignant tumor tissues and can promote the proliferation of tumor cells [12,13], but it has not been reported in the study on the mechanism of diabetes. In patients with diabetes, IGF-1 signal transduction can change the adhesion of cells and lead to malignant development of cells.…”
Section: Immunohistochemistry Analysis Of Igf-1 Expression In Islet Tmentioning
confidence: 99%
“…The Lgals3 gene, which encodes galectin-3, plays an important role in acute and chronic inflammation [27]. The insulin-like growth factor 1 (IGF-1) gene has insulin-like functions and encodes proteins involved in regulating the development and maintenance of the nervous system [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that IGF-1 expression is increased in frontal cortex in PD compared to controls, while IGF1R is reduced in white matter and amygdala [63,64]. As aforementioned, IGF-1 levels and signaling cascade are reduced during aging, due to an increased hyper-phosphorylation of insulin receptor substrates (IRSs), one of the first proteins activated in insulin and IGF-1 pathways, thus impairing the activation of downstream molecules such as PI3K [65][66][67].…”
Section: Expression Of Igf-1 In Central Nervous Systemmentioning
confidence: 99%